Mechanically processed, vacuum- and etch-free fabrication of metal-wire-embedded microtrenches interconnected by semiconductor nanowires for flexible bending-sensitive optoelectronic sensors - Kim Taeyun; Kim Minwook; Han Jinkyu; Jeong Hocheol; Lee Seungmin; Kim Jaeil; Lee Daeho; Jeong Hoon Eui; Ok Jong G. (Nanophotonics, 2024)
We demonstrate the facile fabrication of metal-wire-embedded microtrenches interconnected with semiconducting ZnO nanowires (ZNWs) through the continuous mechanical machining of micrograting trenches, the mechanical embedding of solution-processable metal wires therein, and the metal-mediated hydrothermal growth of ZNWs selectively thereto. The entire process can be performed at room or a very low temperature without resorting to vacuum, lithography, and etching steps, thereby enabling the use of flexible polymer substrates of scalable sizes. We optimize the fabrication procedure and resulting structural characteristics of this nanowire-interconnected flexible trench-embedded electrode (NIFTEE) architecture. Specifically, we carefully sequence the coating, baking, and doctor-blading of an ionic metal solution for the embedding of clean metal wires, and control the temperature and time of the hydrothermal ZNW growth process for faithful interconnections of such trench-embedded metal wires via high-density ZNWs. The NIFTEE structure can function as a bending-sensitive optoelectronic sensor, as the number of ZNWs interconnecting the neighboring metal wires changes upon mechanical bending. It may benefit further potential applications in diverse fields such as wearable technology, structural health monitoring, and soft robotics, where bending-sensitive devices are in high demand.